2013
DOI: 10.1089/gtmb.2012.0201
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of JAK2 and STAT3 Variants to the Genetic Susceptibility of Recurrent Spontaneous Miscarriage in a Tunisian Population

Abstract: STAT3 rs1053023, more so than the STAT3 rs1053004 or JAK2 rs2230724 polymorphisms, is associated with RSM risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
1
2
1
Order By: Relevance
“…These findings were consistent with the data conducted in the recent Chinese cohort (T allele: 65.63% and C allele: 34.37%) (Xie et al, 2013), suggesting that the SNP has homogeneity in the allele distribution among East-Asian (Thai and Chinese) populations. Interestingly, in contrast to our report, the frequency of C allele was higher than T allele in Tunisian Arabs (Middle East) (Messaoudi et al, 2013a;2013b). SNP rs1053004, localized on 3'-UTR of STAT3, regulates expression of STAT3 protein by altering mRNA degradation and decreased STAT3 activity (Foshay and Gallicano, 2009;Xie et al, 2013).…”
Section: Discussioncontrasting
confidence: 98%
“…These findings were consistent with the data conducted in the recent Chinese cohort (T allele: 65.63% and C allele: 34.37%) (Xie et al, 2013), suggesting that the SNP has homogeneity in the allele distribution among East-Asian (Thai and Chinese) populations. Interestingly, in contrast to our report, the frequency of C allele was higher than T allele in Tunisian Arabs (Middle East) (Messaoudi et al, 2013a;2013b). SNP rs1053004, localized on 3'-UTR of STAT3, regulates expression of STAT3 protein by altering mRNA degradation and decreased STAT3 activity (Foshay and Gallicano, 2009;Xie et al, 2013).…”
Section: Discussioncontrasting
confidence: 98%
“…43 Besides, Messaoudi et al, reported that the G allele in rs1053023 polymorphism is associated with recurrent miscarriages in Bahraini and Tunisian Arab populations. 44,45 This result was not surprising, as previous studies revealed higher levels of p-STAT3, IL17, and IL17R in patients with unexplained recurrent spontaneous abortions. 46,47 In another study evaluating the association between these two polymorphisms in STAT3 and the risk of developing noise-induced hearing loss (NIHL), it was demonstrated that the G allele in both variants was linked with NIHL risk.…”
Section: Discussionsupporting
confidence: 54%
“…Yang, H et al. [ 39 ] establish that mouse endometrium expressed CDKN2a gene during early pregnancy and it has a possible role in blastocyst implantation [ 39 ]. Inclusive mechanisms of CDKN2a in inducing apoptosis of the endometrial cells and contact with the other factors that influence the embryo blastocyst implantation required further research.…”
Section: Discussionmentioning
confidence: 99%